Perfil cognitivo en pacientes con infección por el virus de inmunodeficiencia humana neurológicamente asintomáticos - Guevara-Silva, Erik (2013)
Several studies have reported cognitive impairment in HIV-1 infected individuals even at early stages of the infection. Short-term memory, psychomotor speed, attention and executive functions are mainly affected. Objectives: To determine the cognitive profile in neurologically asymptomatic HIV-infected patients before starting highly active antiretroviral therapy (HAART), and possible associated factors. Design: Analytic and cross-sectional study. Setting: Hospital Regional de Huacho, Peru. Participants: HIV patients with criteria to start HAART. Interventions: Twenty-one asymptomatic HIV patients attended from April to July 2011 had a detailed clinical history and a battery of standardized neuropsychological tests. Main outcomes measures: Scores in psychomotor speed, executive function, immediate memory, attention, and visuospatial performance evaluations. Results: Significant cognitive impairment was determined in 47.6% of patients. Patients performed worse in psychomotor speed and executive function tests. All but one patient failed at least in one test. Age, level of instruction, time of disease, and depression were not statistically associated. Conclusions: In accordance with the literature, these findings suggest cognitive decline may occur in early asymptomatic stages of HIV infection.